Atypical nucleus pulposus migration and calcification: A specific radiographic sign for lumbar rheumatoid spondylitis - Haocheng Cui; Jingming Wang; Lei Wang; Xiaoduo Xu; Weimin Huang (PLoS ONE, 2025)
Objective This study aimed to characterize a specific radiographic manifestation of lumbar rheumatoid spondylitis. Methods and materials The patients diagnosed with lumbar rheumatoid spondylitis who underwent posterior lumbar fusion surgery between 1/6/2019 and 30/4/2023 in the Department of Orthopedic Surgery in our hospital were retrospectively studied (RA group). The patients diagnosed with lumbar disc herniation with nucleus pulposus migration (cranial or caudal) were also collected for comparison (control group). The clinical data and radiographic manifestations were compared and analyzed. Results A total of 14 patients in the RA group and 36 patients in the control group were enrolled in the current study. In the RA group, seven patients had nucleus pulposus migration, among whom five patients exhibited distinct calcification (5/7, 71.4%). Of the 36 patients in the control group, 10 patients demonstrated migrated nucleus pulposus calcification (10/36, 27.8%). The migrated nucleus pulposus in the RA patients exhibited diffuse calcification, while the migrated nucleus pulposus in the control group exhibited spot-like or shell-like calcification. In addition, nucleus pulposus migration and calcification in the RA group were more likely to occur in older patients, affect the higher lumbar levels and combine with intervertebral space collapse compared with the control group. Conclusions Nucleus pulposus migration and calcification is specific in RA patients. It may be a characteristic radiographic sign to establish a lumbar rheumatoid spondylitis diagnosis. The potential mechanism is still unclear and need to be further explored.